2016
DOI: 10.3389/fmicb.2016.00292
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Bovine viral diarrhea virus Infection in Three Species of Sympatric Wild Ungulates in Nevada: Life History Strategies May Maintain Endemic Infections in Wild Populations

Abstract: Evidence for bovine viral diarrhea virus (BVDV) infection was detected in 2009–2010 while investigating a pneumonia die-off in Rocky Mountain bighorn sheep (Ovis canadensis, canadensis), and sympatric mountain goats (Oreamnos americanum) in adjacent mountain ranges in Elko County, Nevada. Seroprevalence to BVDV-1 was 81% (N = 32) in the bighorns and 100% (N = 3) in the mountain goats. Serosurveillance from 2011 to 2015 of surviving bighorns and mountain goats as well as sympatric mule deer (Odocoileus hemionus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 30 publications
1
17
0
1
Order By: Relevance
“…Necrotizing mesenteric lymphadenitis prompted testing for BVDV infection. Though BVDV IHC was negative, virus isolation of spleen was positive for BVDV1a confirming current natural infection in a free-living mountain goat (Wolff et al, in press ).…”
Section: What Is the Role Of Bvdv Persistent Infection In Wild Ungulamentioning
confidence: 81%
See 1 more Smart Citation
“…Necrotizing mesenteric lymphadenitis prompted testing for BVDV infection. Though BVDV IHC was negative, virus isolation of spleen was positive for BVDV1a confirming current natural infection in a free-living mountain goat (Wolff et al, in press ).…”
Section: What Is the Role Of Bvdv Persistent Infection In Wild Ungulamentioning
confidence: 81%
“…Serosurvey of the Idaho zoological collection cohorts (including domestic sheep, domestic goats, mule deer, and whitetail deer in the same pen) suggested there may have been transmission between these wild caught mountain goats and the other ruminants, but the origin of this virus was not determined (Nelson et al, 2008 ). Evidence of BVDV infection in domestic cattle and free-living bighorn sheep, mountain goats, and mule deer sharing the same range in Nevada demonstrated interspecies transmission in wild settings (Wolff et al, in press ). Since pestivirus infection causes immunosuppression with increased susceptibility to bacterial infection, BVDV likely played this indirect role in these mountain goats with septicemia.…”
Section: What Is the Role Of Bvdv Persistent Infection In Wild Ungulamentioning
confidence: 99%
“…This pathogen does not act alone but appears to be a necessary agent for initiating epizootics. Further research is needed on the role of co‐infection by known and perhaps as yet unrecognized pathogens as well as other factors that may contribute to disease outcomes by affecting transmission, carriage, and immunity (Dassanayake et al , Besser et al , Fox et al , Wolff et al ). Clarity on the significance of these interactions will help provide a more complete understanding of the variation observed in the course of infection and disease.…”
Section: Causes Of Pneumonia In Bighorn Sheepmentioning
confidence: 99%
“…BVDV infection in small ruminants is similar to those in cattle. Postnatal infections cause mild clinical symptoms, including pyrexia and leukopenia, and infections in pregnant small ruminants may cause reproductive failures [11, 1822]. Our findings revealed that experimental BVDV infection in Korean native goats via IN route showed a normal appearance with only mild respiratory signs such as coughing and nasal discharge and did not cause pyrexia, anorexia, and diarrhea.…”
Section: Discussionmentioning
confidence: 68%
“…In a previous study, we reported BVDV infection in Saanen goats, which exhibited no clinical symptoms [15]. Several studies have demonstrated that clinical manifestation of BVDV infection in sheep and goats may differ depending upon inoculation route, age of the hosts, and the BVDV strain used [1822]. Taken together, BVDV infection in Korean native goats induced via IN inoculation is accompanied only by respiratory symptoms.…”
Section: Discussionmentioning
confidence: 86%